The evolution of hydrophobic cell wall biopolymers from algae to angiosperms - Niklas, Karl J (Journal of experimental botany, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.